Risk factors, mortality trends and cardiovasuclar diseases in people with Type 1 diabetes and controls: A Swedish observational cohort study - Sara Hallström; Magnus Olof Wijkman; Johnny Ludvigsson; Per Ekman; Marc Alan Pfeffer; Hans Wedel; Annika Rosengren; Marcus Lind (Elsevier, 2022)
Summary: Background: Historically, the incidence of cardiovascular disease and mortality in persons with Type 1 diabetes (T1D) has been increased compared to the general population. Contemporary studies on time trends of mortality and cardiovascular disease are sparse. Methods: In this observational study, T1D persons were identified in the Swedish National Diabetes Registry (n=45,575) and compared with matched controls from the general population (n=220,141). Incidence rates from 2002 to 2019 were estimated with respect to mortality and cardiovascular disease in persons with T1D overall and when stratified for prevalent cardiovascular and renal disease relative to controls. Findings: Mean age in persons with T1D was 32.4 years and 44.9% (20,446/45,575) were women. Age- and sex- adjusted mortality rates declined over time in both groups but remained significantly higher in those with T1D compared to controls during 2017-2019, 7.62 (95% CI 7.16; 8·08) vs. 2.23 (95% CI 2.13; 2.33) deaths per 1,000 person years. Myocardial infarction, heart failure and stroke decreased over time in both groups, with persistent excess risks in the range of 3.4-5.0 times from 2017 to 2019 in those with T1D. T1D persons ≥45 years without previous renal or cardiovascular complications had standardized mortality rates similar or even lower than controls 5.55 (4.51; 6.60) vs.7.08 (6.75; 7.40) respectively in the last time period. Interpretation: Excess mortality persisted over time in persons with T1D, largely in patients with cardiorenal complications. Improved secondary prevention with a focus on individualized treatment is needed to close the gap in mortality for individuals with T1D. Funding: This study was financed by grants from the ALF-agreement, NovoNordisk Foundation and the Swedish Heart and Lung Foundation.